Penerapan Work From Home Terhadap Produktivitas Kerja (Studi Karyawan PT Berlian Jasa Terminal Indonesia) - Julika Pasaribu; Mochammad Isa Anshori (Forum Inovasi Bisnis dan Manajemen, 2021)
The object of research was done on employees in Berlian Jasa Terminal Indonesia (BJTI) Port of Surabaya. Methodology this study used a quantitative method, the analysis of multiple regression. The sampling method by using sample random sampling with quantity of respondents as many as 65 respondents who are staff BJTI Port of Surabaya. The study to decide the relationship and impact of the implementation of work from home work productivity of employees BJTI Surabaya. The results of this study prove (1) time has positive and significant on work productivity with value tcount is 13.780 > ttable 1,67065 and significant level has 0,000 < 0,05 ; (2) room (workspace) has positive and significant influence on work productivity with value tcount is 3.215 > ttable 1,67065 and significant level has 0,002 < 0,05 ; (3) role of social has positive and significant influence on work productivity with value tcount is 12.758 > ttable is 1,67065 and significant level has 0,000 < 0,05 ; (4) Together or simultaneously that time, room and role of social has significant effect on work productivity, from the value of Fcount 402.181 > Ftabel 2.76 with significant level 0,000.